Social systems - Luhmann, Niklas, 1927-1998. (Stanford, Calif. : Stanford University Press, 1995)
A major challenge confronting contemporary theory is to overcome its fixation on written narratives and the culture of print. In this presentation of a general theory of systems, Germany's most prominent and controversial social thinker sets out a contribution to sociology that reworks our understanding of meaning and communication.
Luhmann responds to the theory crisis in sociology with a genealogy of his own, which includes a cybernetician (Heinz von Foerster), two evolutionary biologists (Humberto R. Maturana and Francisco Varela), and an obscure mathematician (George Spencer Brown), not to speak of the Devil Himself.
This list of names defines a set of problems that explodes the boundaries of sociology by linking social theory to recent theoretical developments in scientific disciplines as diverse as modern physics, information theory, general systems theory, neurophysiology, phenomenology, and cognitive science. In these fields, the erosion of classical paradigms suggests, not the end of science, but a fundamental revision of its theoretical premises.
Instead of a Preface to the English Edition: On the Concepts "Subject" and "Action" -- Introduction: Paradigm Change in Systems Theory -- 1. System and Function -- 2. Meaning -- 3. Double Contingency -- 4. Communication and Action -- 5. System and Environment -- 6. Interpenetration -- 7. The Individuality of Psychic Systems -- 8. Structure and Time -- 9. Contradiction and Conflict -- 10. Society and Interaction -- 11. Self-Reference and Rationality -- 12. Consequences for Epistemology.
Includes bibliographical references (p. [491]-617) and index.
Keywords: Social systems; Autopoiesis